Comparison Study Between Crude and Purified L-Asparaginase From Bacillus Spp. for Reduction of Acrylamide Level During Fries Processing - H., Sahar I.; H. , Zaid A. (Iraqi Journal of Science, 2024)
Acrylamide is a toxic chemical that is created when foods are heated; it is also available in foods containing different additives. The purpose of the study was to determine whether Bacillus spp. isolates could reduce the concentration of acrylamide in food, as well as to compare the different treatments of crude and pure L-asparaginase produced from the same bacteria in acrylamide reduction in potato slices. Our findings reveal that this bacterium could degrade acrylamide and reduce its concentration. Furthermore, the acrylamide content of potato slices reduced dramatically with increasing enzymatic treatment time, reaching the under detection limit (UDL) after 30 minutes of treatment with 84 U/ml of crude and purified L-asparaginase. In addition, the purified enzyme is more active in removing acrylamide from potato slices than the crude enzyme at all three times. The removal efficiency rises as the enzyme concentration increases. After bleaching the potato slices for 20 minutes at 80 °C with 84 U/ml of pure enzyme, the acrylamide level was totally decreased.